Transcorporalidade silicone industrial e processo transexualizador - Rego, Joelson Xavier do (2018)
The trans women in their experience seek to construct their identity as a woman following the prescriptions socially postulated, adjusting their bodies in order to give shape to a female body. In this process, they use, among other resources, industrial silicone, which has numerous side effects. The main objective of the present research was to understand the meanings of the use of industrial silicone for the production of the feminities of trans women, and to describe the consequences of the use of industrial silicone for their health and to identify the main demands of trans women in seeking the specialized service in the process transexualizador of SUS in the State of Paraná. Participants were 13 trans women who had used industrial silicone, ranging in age from 21 years to 59 years. These women were invited to participate in a larger study, the Divas survey, held in Curitiba/PR, in the 2nd Regional Metropolitan Health (Metropolitan CRE). The semi-structured interview was used as a data collection instrument because it was an interview with relatively open planning. The analysis of the collected data was made through the content analysis, and after a first reading of this material the analysis came from the following categories and subcategories: a) the construction of female bodies and experiences, a1) side effects of industrial silicone; b) the process of feminization in the transsexualization process of SUS. Corroborated for material analysis the vulnerability framework and human rights, as well as specialized literature. Through this analysis, it was possible to verify the importance of the use of industrial silicone in the process of constructing their bodies, even in the face of the risks caused due to their use and that the specialized service in the transsexualization process by the SUS in Paraná, CPATT, does not produce the reduction of these vulnerabilities to illness, since the service is offered only at the outpatient level, not providing access to the surgeries demanded by the interviewees, and thus collaborating so that they do not remain in the service. For this reason, there is an increase in the vulnerabilities to illness, being essential the implantation of the service in hospital level.